Biomechanical and organisational stressors and associations with employment withdrawal among pregnant workers: evidence and implications. Issue 12 (1st December 2016) - Guendelman, Sylvia; Gemmill, Alison; MacDonald, Leslie A.
Abstract: The distribution of exposure to biomechanical and organisational job stressors (BOJS) and associations with employment withdrawal (antenatal leave, unemployment) was examined in a case-control study of 1114 pregnant workers in California. We performed descriptive and multivariate logistic and multinomial regression analyses. At pregnancy onset, 57% were exposed to one or more biomechanical stressors, including frequent bending, heavy lifting and prolonged standing. One-third were simultaneously exposed to BOJS. Exposure to biomechanical stressors declined as pregnancy progressed and cessation often (41%) coincided with employment withdrawal (antenatal leave and unemployment). In multivariate modelling, whether we adjusted for or considered organisational stressors as coincident exposures, results showed that pregnant workers exposed to biomechanical stressors had increased employment withdrawal compared to the unexposed. Work schedule accommodations moderate this association. Paid antenatal leave, available to few US women, was an important strategy for mitigating exposure to BOJS. Implications for science and policy are discussed. Practitioner Summary: This case-control study showed that exposure to biomechanical stressors decline throughout pregnancy. Antenatal leave was an important strategy used for mitigating exposure among sampled California women with access to paid benefits. Employment withdrawal among workers exposed to BJOS may be reduced by proactive administrative and engineering efforts applied early in pregnancy.